EVALUASI PELAKSANAAN PROGRAM USAHA KESEHATAN GIGI SEKOLAH (UKGS) DI SEKOLAH DASAR WILAYAH KERJA PUSKESMAS OLAK KEMANG KOTA JAMBI: Evaluation of Implementation of School Dental Health Program (UKGS) in Elementary School at Olak Kemang Public Health Center Working Area, Jambi - Nurchafifah, Evi; Fitri, Adelina; Nurchafifah, Guspianto (Poltekes Kemenkes Tanjungpinang, 2021)
The prevalence of dental caries problems in Jambi City was 0.74%. And the highest number of cases per kelurahan that had dental caries problems occurred in Olak Kemang Health Center in Jambi City, which was 6.81%. There are several obstacles in the implementation of the UKGS program in the working area of ​​the Olak Kemang Health Center in Jambi City, where HR is not in accordance with standards, facilities and infrastructure are inadequate, budget funds are minimal. This study was use qualitative research methods with a case study design. Data collection through in-depth interviews, Focus Group Discussion (FGD), observation and documentation. Checking the validity of the data utilized source triangulation techniques and methods. The results of the evaluation of the UKGS program showed that some aspects of the input have not met the standards, which consist of UKGS implementing staff in schools, budget funds, facilities and infrastructure and SOP contributions in schools. Coverage Program UKGS Activities carried out only education / counseling and examination of teeth and mouth, for coaching / training Output in the UKGS program activities is the knowledge of students about UKGS and dental and mouth health is very poor.The implementation of the UKGS program in the work area of ​​the Puskesmas Olak Kemang has not been maximized, which results in less than optimal performance of the UKGS implementers.